2017
DOI: 10.1093/her/cyx059
|View full text |Cite
|
Sign up to set email alerts
|

Motivating parent support for physical activity: the role of framed persuasive messages

Abstract: Parent support for physical activity (PA) is a behavior unto itself that requires motivation. Persuasive messages may be one method for motivating parent support for their children's PA. Message framing is one strategy for optimizing the impact of messages. The current study examined the relative effectiveness of gain- versus loss-framed messages for encouraging parent support for children's PA. Regardless of message frame, parents had an increase in social cognitive antecedents (e.g. perceived behavioral cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…One approach to understanding parental support has been to employ behavioural theory. Most of this work has been performed using an adaptation of Ajzen's () theory of planned behaviour (TPB) in the PA domain and the results have shown general support of this structure in both observational (Rhodes et al., , ) and experimental research (Bassett‐Gunter, Stone, Jarvis, & Latimer‐Cheung, ; Laukkanen, Pesola, Finni, & Sääkslahti, ). Despite the general evidence for the utility of this TPB framework, the relationship between intention and support behaviour has been modest.…”
Section: Introductionmentioning
confidence: 91%
“…One approach to understanding parental support has been to employ behavioural theory. Most of this work has been performed using an adaptation of Ajzen's () theory of planned behaviour (TPB) in the PA domain and the results have shown general support of this structure in both observational (Rhodes et al., , ) and experimental research (Bassett‐Gunter, Stone, Jarvis, & Latimer‐Cheung, ; Laukkanen, Pesola, Finni, & Sääkslahti, ). Despite the general evidence for the utility of this TPB framework, the relationship between intention and support behaviour has been modest.…”
Section: Introductionmentioning
confidence: 91%
“…PA is fun and cool) in this population. Although one experimental study found no advantage for gain-framed messages over loss-framed in encouraging parent's support for child PA [37], evidence from existing reviews and qualitative research generally supports the use of gain-framed messages when focusing on children or their parents [17,33,38]. Messages targeting cognitive antecedents of PA specified by Theory of Planned Behaviour (e.g.…”
Section: Children and Young People Message Contentmentioning
confidence: 99%
“…In parents of disabled children, qualitative research has revealed that preferred PA message providers are reliable and credible organisations, other parents [37], and the school [138]. Role models (e.g.…”
Section: Message Deliverymentioning
confidence: 99%
“…Parents within this study described feeling overwhelmed in trying to keep up with the many demands placed on them, a common experience in the cancer treatment setting 46 . Assessing parental knowledge, motivation, and perceived barriers to physical activity, for example through survey questions derived from the theory of planned behavior, 47 could inform the provision of targeted education and supportive care, and enable parents to be more effective advocates of physical activity. Models of care that emphasize the parental role in physical activity promotion could provide guidance in achieving this.…”
Section: Discussionmentioning
confidence: 99%